The global governance of knowledge creation and diffusion - Hveem, Helge; Iapadre, Lelio (New York, NY : Routledge, 2011)
"There is an increasing scientific and political sensibility for questions regarding the "governance of a knowledge society" and the societal benefits and problems of a "knowledge economy". The International Regulation of Knowledge utilises case studies and a comparative country / thematic approach to prove a compehensive survey of the regulation and governance of knowledge flow, research and innovation. By identifying activities creating new knowledge (e.g. education, migration), it demonstrates how knowledge regulation and diffusion works in practice and policy. The book will be of interest to students and scholars of globalization, international relations and policy regulation"-- Provided by publisher.
"The Global Governance of Knowledge provides a survey and analysis of international agreements and institutions, global and regional, which regulate the creation and dissemination of knowledge"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Higher education -- International cooperation; Technology transfer